2020
DOI: 10.35848/1882-0786/abca7c
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy cross-sectional cathodoluminescence analysis of the depth distribution of point defects in Si-ion-implanted β-Ga2O3

Abstract: Low-energy cross-sectional cathodoluminescence (CL) with a beam energy of 1 keV was applied to Si-ion-implanted β-Ga2O3 (−201) wafers to investigate implantation damage and recovery. The semi-quantitative CL-intensity depth profiles were obtained by considering nonradiative recombination at the surface. We found that the CL intensity did not fully recover, even after annealing at 1273 K. Such insufficient recovery was prominent in the Si-diffusion region, suggesting that Si-dopant activation and Si diffusion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…The corresponding calculated vacancy profiles peaked at ∼200 nm. Previous work in the literature has shown that SRIM calculations of the depth distribution for Si-implantation in β-Ga2O3 corresponds well with experimental measurements 16,24 .…”
Section: Resultssupporting
confidence: 79%
“…The corresponding calculated vacancy profiles peaked at ∼200 nm. Previous work in the literature has shown that SRIM calculations of the depth distribution for Si-implantation in β-Ga2O3 corresponds well with experimental measurements 16,24 .…”
Section: Resultssupporting
confidence: 79%
“…The blue-band emission around 3.0 eV of β-Ga 2 O 3 was strongly observed, as reported in other literature. 23,27) Notably, the luminescence property of this β-Ga 2 O 3 thin film prepared on the polymer substrate by ELA treatment at RT was close to that of single crystalline β-Ga 2 O 3 .…”
mentioning
confidence: 58%
“…VUV excitation is effective for UWBG semiconductors; however, VUV systems require a special spectrometer and light source, and the operation conditions are only met in a synchrotron radiation beamline. Cathodoluminescence (CL), which uses electron beams, is suitable for defect characterization in UWBG semiconductors because conventional scanning electron microscope (SEM) can be used as the excitation source, and the exciting-beam energy exceeds the bandgap energies of UWBG semiconductors [11,[18][19][20][21][22]. We reported CL analysis on the Si-ion-implanted β-Ga2O3 [22]; however, only a cross-sectional measurement at a dose of 1 × 10 15 cm −2 , which was relatively high dose implantation, are show in in the report.…”
Section: Introductionmentioning
confidence: 99%
“…For the crosssectional CL measurements, we used the cleavage (100) surface instead of mechanically polished faces to avoid processing damage due to cutting. The detailed experimental conditions of the cross-sectional measurements were described in [22].…”
Section: Introductionmentioning
confidence: 99%